Fecal metabolomics to understand intestinal dysfunction in male dairy beef calves at arrival to the rearing farm - Anna Bassols; Núria Amigó; Marc Pérez-Rodado; Yolanda Saco; Raquel Peña; Raquel Pato; Lucia Pisoni; Maria Devant; Sònia Marti (Scientific Reports)
Abstract Fecal biomarkers are becoming an important analytical tool since feces are in direct contact with the inflamed intestine and site for the gut microbiome. The objective of this study was the identification of differential fecal metabolites by means of 1H-NMR to evaluate the management of male dairy beef calves, and which could become potential biomarkers of gastrointestinal disorders. Holstein calves were subjected to a protocol aimed to simulate real conditions of the dairy beef market. Three groups were studied: Control (CTR: high colostrum, no transport, milk replacer), LCMR (low colostrum, transport, milk replacer) and LCRS (low colostrum, transport, rehydrating solution). Fecal lactoferrin was determined as marker of intestinal inflammation, and metabolomic profiling was performed in feces collected the day after arrival to the farm. 41 polar and 10 non-polar metabolites were identified, of which proline, formate and creatine increased in the LCRS group, whereas butyrate and uracil decreased. Less differences were found in non-polar metabolites. Multivariate analysis indicated that most differences are found between the LCRS group and the others. In conclusion, this study indicates that feed restriction has a more important effect at this age than colostrum uptake and transport. These results should help to identify robust fecal biomarkers to assess calf intestinal health and improve management protocols.